2021
DOI: 10.5960/dzsm.2020.474
|View full text |Cite
|
Sign up to set email alerts
|

Declaration of analgesics on Doping Control Forms in german football leagues during five seasons

Abstract: Problem: The use of analgesics in sport has been the subject of numerous studies and surveys among athletes for years. This evaluation was targeted at providing the first evaluation of analgesics declared on Doping Control Forms (DCF) from football players in the highest German leagues, the Cup, and the A and B Juniors’ Bundesliga. Methods: The evaluation included a total of 8,344 DCF from doping controls performed by the National Anti Doping Agency Germany in the five football seasons from 2015/16 to 2019/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At the 2018 men's World Cup, 40% of players used NSAIDs at some point during the tournament while 17% used other forms of analgesics (Oester et al, 2019). At a national elite level, data from the German Bundesliga found that 32% of in-competition doping control forms declared the use of some form of analgesic with the NSAID, ibuprofen, being the most frequently reported (Trinks et al, 2021). Evidently, NSAIDs are commonly used and readily available to players from team medical staff and carry significant side effects if misused.…”
Section: Physical Capital and Painkiller Use In Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 2018 men's World Cup, 40% of players used NSAIDs at some point during the tournament while 17% used other forms of analgesics (Oester et al, 2019). At a national elite level, data from the German Bundesliga found that 32% of in-competition doping control forms declared the use of some form of analgesic with the NSAID, ibuprofen, being the most frequently reported (Trinks et al, 2021). Evidently, NSAIDs are commonly used and readily available to players from team medical staff and carry significant side effects if misused.…”
Section: Physical Capital and Painkiller Use In Footballmentioning
confidence: 99%
“…NSAIDs legal status means players may also purchase and consume these privately (Cunningham, 2018; Mundie and Jurejko, 2017). Recent evidence indicates that painkiller misuse exists in professional, lower-league, junior, and women's football (Babwah, 2014; Correctiv, 2020; Trinks et al, 2021; Tscholl et al, 2015). To be clear, there are legitimate reasons for painkiller use and not all players taking painkillers are misusing them.…”
mentioning
confidence: 99%
“…Using information about self-declared use of pharmaceuticals from DCFs is nothing new and has been used in several other studies ( 10 , 54 , 55 ). However, in the present study, the ATC system was used for classification of the pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%